Students in Name Only: Improving the Working Conditions of Articled Students Via the Application of the BC Employment Standards Act - Blair, Chase (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2022)
Articled students in Canada tend to be exempt from provincial employment standards legislation, which govern minimum hourly wages and overtime and statutory holiday pay rates. Exemption from these provisions, along with the strong power dynamic present in the articled student-principal relationship, has fostered exploitative working conditions for articled students. To justify the exclusion of articled students from employment standards legislation, supporters of the status quo have propagated the narrative that articled students’ labour is not that of an employee, despite evidence to the contrary. In recent years, advocates have proposed various reforms to improve the working conditions of articled students, but they have not targeted employment standards legislation itself. With a focus on British Columbia, this article argues that a better solution to improve the working conditions of articled students is to apply the base provisions of the Employment Standards Act. Further, on closer examination, assertions that such an approach is contrary to the public interest are more rhetorical than substantive.